High school Physics teachers’ perceptions of the learning revolution era 4.0 at training activities in Bener Meriah Regency - Elisa, E; Farhan, A; Herliana, F; Wahyuni, A; Susanna, S (Journal of physics. Conference series, 2021)
The constraints of the limited practicum facilities for Physics lessons in Bener Meriah Regency High School schools can be overcome by virtual laboratory practicum. Learning technology using a virtual laboratory experiment method based on Smart Phone is given to Physics teachers in the district so that they can use simple information technology applications in learning. The subject matter of physics used in this training was Waves and Optics. This activity is gradually carried out to pioneer the realization of physics learning in high schools following the demands of the industrial era 4.0. The output is expected to improve the pedagogical quality of teachers, the learning process, and to overcome the limitations of Physics practicum tools, and to support online learning during the Covid-19 pandemic. The activity was attended by 10 high school teachers in Bener Meriah Regency. All participants were able to master the transfer of technology provided. They are optimistic that this IT technology can be implemented in the learning of Wave and Optical material Physics in their schools on duty. 100% of trainees are satisfied with the service and expect will be any similar activities to be continued for other Physics materials.